Maniema: le pays des mangeurs d'hommes - Cornet, René-Jules (L. Cuypers, 1952)
Don John C. Wilkinson (mars 2026)
Keywords: Tippo Tip (1837-1905)

Les réseaux marchands arabes et swahili en Afrique orientale - Kagabo, Jose (Marchands et hommes d'affaires asiatiques: dans l'océan Indien et la mer de Chine 13e-20e siècles, 1988)
Keywords: Commerce – Oman; Commerce – Zanzibar – 19e siècle; Tippo Tip (1837-1905)

La question arabe et le Congo, 1883-1892 - Ceulemans, P. (Académie royale des sciences coloniales, 1959)
Keywords: Relations – Oman – Congo; Tippo Tip (1837-1905)

Renault (François) : Tippo Tip. Un potentat arabe en Afrique centrale au XIXe siècle - Prunier, Gérard (Outre-Mers. Revue d'histoire, 1988)
Keywords: Recension; Tippo Tip (1837-1905)

The Inscribed Sandals of Tippu Tip - Page, Melvin; Bennett, Patrick (Journal des africanistes, 1972)
Keywords: Tippo Tip (1837-1905); Zanzibar

The autobiography of hamed bin Muhamed el Murjebi, 'tippu tip' - Downing, Angela (Bells: Barcelona English language and literature studies, 1989)
Keywords: Tippo Tip (1837-1905); Zanzibar

Tippo Tip: Un potentat arabe en Afrique centrale au XIXe siecle - Newbury, David (The American Historical Review, 1989)
Keywords: Recension; Tippo Tip (1837-1905)

Autobiographie des Arabers Schech Hamed bin Muhammed el Murjebi, genannt Tippu Tip - Brode, Heinrich (Mittheilungen des Seminars für Orientalische Sprachen an der königlichen Friedrich Wilhelms-Universität zu Berlin, 1902)
Keywords: Tippo Tip (1837-1905); Zanzibar

Tippoo Tib, the story of his career in Central Africa - Brode, Heinrich (Edward Arnold, 1907)
Keywords: Tippo Tip (1837-1905); Zanzibar

Tippu Tip: Lebensbild eines zentral-afrikanischen Despoten - Brode, Heinrich (Baensch, 1905)
Keywords: Tippo Tip (1837-1905); Zanzibar

Tippo Tip: un potentat arabe en Afrique centrale au XIX ^e siècle. Par François Renault. Paris: Société Française d'Histoire d'Outre-Mer, 1987. Pp. 361. 220 F. - Bennett, Norman Robert (The Journal of African History, 1989)
Keywords: Recension; Tippo Tip (1837-1905)

Tippo Tip à Mulongo. Nouvelles données sur le début de la pénétration arabo-swahili au Sahara - Maret, Pierre de; Legros, Hugues (Civilisations. Revue internationale d’anthropologie et de sciences humaines, 1993)
The tribal lands of the Luba of Mulongo, situated at the extreme north of the Upemba depression are not only an almost obligatory point of passage for those coming from the east en route to the heart of the Luba but are also an important market. It is therefore a very useful place to study the Arab-Swahili penetration in the kingdom of Luba in the nineteenth century, especially as one of the first merchants to reach this chefferie was none other than Tippo Tip. In his autobiography, he briefly speaks of his incursions in Luba but up to now, no other source has permitted the verification or the completion of the information provided by Tippo Tip.An unpublished administrative report dating from 1909, written up from the oral tradition of the precedent century, tells of power struggles between two rival lineages of the Mulongo royalty. The report not only provides a complete ancestry of the chiefs but also allows the accurate dating of the stages of Arab-Swahili penetration in the kingdom of Luba. Furthermore, this document refers to the passage of Tippo Tip in the region and gives us much information regarding the events that took place during his stay. The congruence of the sources enables a relatively detailed chronology of the passage of Tippo Tip to be established and a better definition of the forms of the penetration and the political domination of Arab-Swahili at the heart of the Luba empire.
Keywords: Tippo Tip (1837-1905); Zanzibar

Tippo-Tip - Moeller de Laddersous, A. (Biographie coloniale Belge, 1948)
Keywords: Tippo Tip (1837-1905)

The Mysore grants, 1860: The appeal of Tippu Sultan's son - Knight, L.A. (South Asia: Journal of South Asian Studies, 1978)
Keywords: Tippo Tip (1837-1905)

Maisha ya Hamed bin Muhammed el Murjebi: yaani Tippu Tip, kwa maneno yake mwenyewe - Brode, Heinrich (East African Swahili Committee Journals, 1958)
Keywords: Tippo Tip (1837-1905); Zanzibar

Review of L'autobiographie de Hamed ben Mohammed el-Murjebi Tippo Tip (ca. 1840-1905), François Bontinck - Roberts, Andrew (Africa: Journal of the International African Institute, 1976)
Keywords: Recension; Tippo Tip (1837-1905)

Tippu Tip and the East African Slave Trade - Farrant, Leda (Hamish Hamilton, 1975)
Keywords: Esclavage – Zanzibar; Tippo Tip (1837-1905)

Murḏj̲ibī al- - Sicard, S. von (Encyclopédie de l'Islam, 1993)
Ḥāmid b. Muḥammad al-Murd̲j̲ibī, alias Tippu Tip, naquit à Zanzibar vers 1837 d’ascendance afroarabe. Son arrière-grand-père, Rad̲j̲ab b. Muḥammad b. Saʿīd al-Murd̲j̲ibī, originaire de Masḳaṭ [q.v.], s’était lui-même établi sur la côte opposée, à Zanzibar, où il avait épousé une femme afro-arabe, fille d’un membre du célèbre clan Nabhānī, Ḏj̲umaʿ b. Muḥammad al-Nabhānī.
Keywords: Biographies – Zanzibar; Tippo Tip (1837-1905)

Tippu Tip, Livingstone, and the Chronology of Kazembe - Roberts, Andrew (Azania: Archaeological Research in Africa, 1967)
Dr. Roberts has been working on the oral history of the Bemba of Zambia. He is now Research Fellow in Oral History at the University College, Dar es Salaam. In this paper he examines crucial points bearing on the chronology of Zambian history, and puts in a plea for a similar re-examination of other supposed exact dates which are in circulation; a plea which we also would heartily support in respect of the early history of the coast as well as that of the interior.
Keywords: Tippo Tip (1837-1905); Zanzibar

La mission politique de Jérôme Becker auprès de Tippo Tip (1888-1889) - Salmon, Pierre Marcel (Cahiers africains, 1993)
Keywords: Tippo Tip (1837-1905); Zanzibar

Mohammed ben Juma el-Murjebi, père de Tippo Tip - Bontinck, François (Bulletin des séances / Académie Royal des Sciences d'Outre-Mer, 1979)
Keywords: Tippo Tip (1837-1905); Zanzibar

Tippo Tip, traitant et organisateur d'Etat - Kinenge, Kimena Kekwaka (Zaïre-Afrique : économie, culture, vie sociale Zaïre-Afrique, 1979)
Keywords: Tippo Tip (1837-1905); Zanzibar

The sound of guns: a biography of Tippu Tip - Monahan, Merry Patricia (San Francisco State College, 1972)
Keywords: Tippo Tip (1837-1905); Zanzibar

La Vie de Disasi Makulo: ancien esclave de Tippo Tip et catéchiste de Grenfell - Makulo, Disasi; Makulo, Akambu; Verhaegen, Bernard (Éditions Saint Paul Afrique, 1983)
Keywords: Esclavage – Zanzibar; Tippo Tip (1837-1905)

Le véritable sens des surnoms africains de Tippo Tip - Bontinck, François (Annales Aequatoria, 1999)
Keywords: Tippo Tip (1837-1905); Zanzibar

Tippo Tip, traitant et sultan du Manyema - Kinenge, Kimena Kekwaka (Centre de recherches pédagogiques, 1979)
Keywords: Tippo Tip (1837-1905); Zanzibar

L'autobiographie de Hamed ben Mohammed el-Murjebi Tippo Tip (ca. 1840-1905) - Tippo Tip; Bontinck, François; Janssen, Koen (Académie royale des sciences d'outre-mer, 1974)
Keywords: Tippo Tip (1837-1905); Zanzibar

Maisha ya Hamed bin Muhammed el Murjebi: yaani Tippu Tip, kwa maneno yake mwenyewe - Brode, Heinrich (East African Literature Bureau, 1974)
Keywords: Tippo Tip (1837-1905); Zanzibar

Tippo Tip: un potentat arabe en Afrique centrale au XIXe siècle - Renault, François (Société française d'histoire d'outre-mer : Diffusion, L'Harmattan, 1987)
Keywords: Tippo Tip (1837-1905); Zanzibar

Review of Tippo-Tip: un potentat arabe en Afrique centrale au XIXe siècle - Moulin, Léon de Saint (Canadian Journal of African Studies, 1991)
Keywords: Recension; Tippo Tip (1837-1905); Zanzibar